2008
DOI: 10.1089/clo.2008.0004
|View full text |Cite
|
Sign up to set email alerts
|

Germinative Testicular Cells and Bone Marrow Mononuclear Cells Transplanted to a Rat Model of Testicular Degeneration

Abstract: The aim of this study was to evaluate the ability of rat mononuclear bone marrow cells to recover testis cell associations and multiplication in busulfan-treated rats, and to compare these data to germinative testicular cell transplant. The germinative testicular cells were obtained by the trypsin digestion method, and bone marrow cells were harvested from femurs and tibias, and purified using by Ficoll gradient. Cell transplantation was performed by the injection of cells through the efferent ducts into the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Transplantation studies on the effects of MSCs on reconstruction of testicular germinal epithelium in infertile male animals, showed a number of promising results. Some studies reported that MSCs had no positive effects on regeneration of germinal epithelium, nor could differentiate into GCs in the testis (25, 26). However others reported that transplanted MSCs not only had the potency for differentiation into GCs (28), but also they could fully differentiate into sperm and regenerate spermatogenesis (27, 29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transplantation studies on the effects of MSCs on reconstruction of testicular germinal epithelium in infertile male animals, showed a number of promising results. Some studies reported that MSCs had no positive effects on regeneration of germinal epithelium, nor could differentiate into GCs in the testis (25, 26). However others reported that transplanted MSCs not only had the potency for differentiation into GCs (28), but also they could fully differentiate into sperm and regenerate spermatogenesis (27, 29).…”
Section: Discussionmentioning
confidence: 99%
“…Although, no study reported similar quantitative data, in total, controversial reports existed regarding the viability of MSCs after transplantation into testes. A group of researchers have stated that MSCs could not survive in the testis (25), whereas others have shown that MSCs were alive 2 months after transplantation (2729). This finding showed that, transplanted BM-MSCs decreased (died and absorbed) with progression of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within two weeks, cultured BMSCs had proliferated to reach 80-90% confluence. Therefore, the shape of the proliferation curves obtained had an inverted "S" shape ( Figure 4), based on the slow proliferation that occurred 0-2 days after inoculation, followed by a period of exponential growth over days [8][9][10][11][12][13]. Consistent with the morphology of the 12 Gy-treated cells versus control cells, the rates of cell proliferation were also found to be similar for cells from group D versus group E (Figure 4).…”
Section: Effect Of Local Irradiation On Bmscsmentioning
confidence: 99%